Serum Growth Factors in Schizophrenia Patients - Anastasiia S. Boiko; Irina A. Mednova; Elena G. Kornetova; Nikolay A. Bokhan; Svetlana A. Ivanova (Current Issues in Molecular Biology, 2023)
Some hypotheses include schizophrenia as a neurodevelopmental disorder, which indicates a special role in growth factors and neuroglia in the development of schizophrenia symptoms. Growth factors are cytokine molecules that play an important role in the regulation of tissue nucleation, cell development, survival, and migration of all tissues in organisms, including the brain and nervous system. The aim of the study was to determine the serum concentration of six growth factors (EGF, VEGF, FGF-2, TGF-α, PDGF-AA, PDGF-AB/BB) in schizophrenia patients and to identify the correlations with clinical characteristics. After signing an informed consent form, 236 schizophrenia patients (F20 according to the ICD-10) and 102 healthy people were recruited in the study. In patients with schizophrenia, we observed a significant elevation in the TGF-α and PDGF-AA serum levels. The duration of schizophrenia was significantly positively correlated with the FGF-2 level. The PANSS total score had a positive correlation with the FGF-2 level and a negative correlation with the TGF-α level. Our results and literature indicate the involvement of growth factors in the mechanisms of development of schizophrenia. Combined biomarker screening seems to be necessary to improve diagnosis and clinical follow-up of patients with severe mental illnesses.